If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-3n + 1) = 64 Reorder the terms: 4(1 + -3n) = 64 (1 * 4 + -3n * 4) = 64 (4 + -12n) = 64 Solving 4 + -12n = 64 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -12n = 64 + -4 Combine like terms: 4 + -4 = 0 0 + -12n = 64 + -4 -12n = 64 + -4 Combine like terms: 64 + -4 = 60 -12n = 60 Divide each side by '-12'. n = -5 Simplifying n = -5
| -8x+30=62 | | 7(x+7)=7 | | X^3-225=0 | | log(4)(x)+log(8)(x^2)=3 | | 0.6r=-78 | | 8(7x-1)=-8 | | 10x+70=90 | | 5-6(x-3)=10 | | 11x+21=142 | | -2m-7=2m+5 | | (x^6)-(x^3)-(6)=0 | | -3(6+5k)-k=-34 | | 5(a+4)-6(4c^2+6-9a)= | | 3y+z=13 | | 3(2x+2)=9x+3-3x+3 | | l=ol | | x+90+x+90+x=360 | | -8a+5a=12 | | lo=l | | 180+4n=360 | | .75x^2-.25x=.50 | | -3x+5=-4x | | 180=(s-2)(180) | | bitch-2397819=589426925 | | 5x+53=113 | | 4(3x-5)=5(2x+7) | | -15=8x^2-22x | | -3.5x^2+60x-200=0 | | penis=8-12 | | 1+7x-5=17 | | 7x-15=90 | | 12(3+m)=5(2m-3) |